Representation of Muna Language Wisdom in Nature Conservation: An Ecolinguistic Perspective - Hadirman, Hadirman (International Journal of Humanities, Education, and Social Sciences, 2024)
This research aims to provide language wisdom in the form of expressions in preserving the natural environment. This research reveals how these communities care for and treat natural resources, especially rivers and sacred forests, in the context of environmental and cultural sustainability. This research method uses a qualitative descriptive approach. The research results show that the Muna people have a close connection with nature, where they consider rivers and sacred forests as spiritual heritage that must be well protected. Traditional rules that protect water sources and holy forests are the basis for the Muna people in maintaining ecological balance and avoiding actions that could damage the natural environment. Verbal expressions in the Muna language also reflect local wisdom values related to the natural environment, such as the prohibition of cutting trees around rivers or sacred forests.